2020
DOI: 10.1590/1678-4685-gmb-2019-0229
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of klotho suppresses growth and pulmonary metastasis of osteosarcoma in vivo

Abstract: Klotho is originally discovered as an anti-aging gene and knock-out of klotho accelerates aging in mice. Subsequent studies support the anti-carcinogenesis role of klotho in a variety of human malignancies. The present study investigated the role of klotho on growth and metastasis of osteosarcoma cells. The osteosarcoma cells were transduced with lentivirus particles encoding klotho or scramble control. The reconstructed osteosarcoma cells were injected into the femoral medullary cavity of nude mice to establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The association of metastasis with lymph nodes is frequently observed in studies that deal with breast cancer ( 83 , 84 ). Studies have demonstrated the importance of Klotho in inhibiting metastasis in mice ( 26 , 85 ). Due to the results of previous studies, Klotho was expected to have an important function in protecting patients against tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…The association of metastasis with lymph nodes is frequently observed in studies that deal with breast cancer ( 83 , 84 ). Studies have demonstrated the importance of Klotho in inhibiting metastasis in mice ( 26 , 85 ). Due to the results of previous studies, Klotho was expected to have an important function in protecting patients against tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…The positive association between Klotho expression and tumour progression is likely because of Klotho's role in cancer development. Human studies on cervical cancer, 37 osteosarcoma, 38 and renal cell carcinoma 39 have shown that Klotho inhibits cell proliferation, migration and invasion. ALT is a liver‐specific cytosolic enzyme, which is elevated with hepatocellular injury.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we reported the inverse correlation between the α-Klotho gene expression and the stage of DTC (p = 0.026), as well as the tumor size (p < 0.001). Li and his colleagues [35] had injected the mice with transduced osteosarcoma cells with overexpressed α-Klotho to evaluate the effect of α-Klotho on tumor growth. After 4 weeks, they had found that α-Klotho overexpression significantly diminished the tumor weight and volume in the mice model of osteosarcoma, compared to controls.…”
Section: Discussionmentioning
confidence: 99%